Hydration reminder: a prototype for a medical instrumentation and electronics course - Triatmaja, Adhy Kurnia; Setyanto, Barry Nur; Ihsana, Nuni (Jurnal Taman Vokasi, 2024)
This article discusses the development of a hydration reminder device aimed at encouraging regular water intake. Created within an Outcome-Based Education (OBE) framework in a medical instrumentation and electronics course, the prototype is designed using the ADDIE model for systematic development. The device, which has reached a Technology Readiness Level (TRL) of 3, features a user-friendly interface and gender-specific hydration metrics to improve personal health management. This interdisciplinary approach integrates educational goals with practical health benefits, anticipating the device's application in both academic settings and everyday use. Plans for intellectual property registration and academic dissemination aim to broaden the project's impact.